Comparison of two different cooling systems in alleviating thermal and physiological strain during prolonged exercise in the heat. Issue 1 (2nd January 2021) - Keller, Sebastian; Kohne, Simon; Bloch, Wilhelm; Schumann, Moritz
Abstract: This study compared the efficacy of an ice vest comprising of water (WATER) or a water-carbon (CARBON) emulsion on thermophysiological responses to strenuous exercise in the heat. Twelve male cyclists completed three 50-minute constant workload trials (55% of peak power output, ambient temperature 30.4 ± 0.6°C) with WATER, CARBON, and without ice vest (CONTROL), respectively. The increase in core body temperature (Tcore) was lower in WATER at 40 (−0.49 ± 0.34 °C) and 50 minutes (−0.48 ± 0.48 °C) and in CARBON at 30 (−0.41 ± 0.48 °C), 40 (−0.54 ± 0.51 °C), and 50 minutes (−0.67 ± 0.62 °C) as compared to CONTROL ( p < 0.05, ES > 0.8). While heart rate and blood lactate kinetics did not differ between the conditions, statistical main effects in favour of both WATER and CARBON were found for thermal sensation (condition p < 0.001 and interaction p < 0.01) and rating of perceived exertion (condition p < 0.05). Per-cooling with CARBON and WATER similarly reduced Tcore but not physiological strain during prolonged exercise in the heat. Practitioner Summary: Exercise in the heat is characterised by increases in thermophysiological strain. Both per-cooling with a novel carbon-based and a conventional water-based ice vest were shown to reduce core temperature significantly. However, due to its lower mass, the carbon-based system may be recommended especially for weight-bearing sports.